The split notochord syndrome with dorsal enteric fistula. - Hoffman, C H; Dietrich, R B; Pais, M J; Demos, D S; Pribram, H F (American Journal of Neuroradiology, 1993)
Split notochord syndrome with dorsal enteric fistula is an extremely rare congenital anomaly that may be associated with meningomyelocele or meningocele, and genitourinary anomalies. This case presented with an additional finding of bladder exstrophy, raising the possibility of a relationship between this syndrome and the OEIS complex.